Predicting the performance of a micro gas turbine under solar-hybrid operation. (15th June 2019) - Ssebabi, Brian; Dinter, Frank; van der Spuy, Johan; Schatz, Markus
Abstract: There are currently no commercial solar-hybrid gas turbine systems readily available off-the-shelf. Several operation and control challenges still exist, and significant development effort is still required to provide technically proven units. To address this gap, this study modeled the performance of a solar-hybrid micro gas turbine (MGT) system, considering both steady-state and transient operation. Based on the component matching, the equilibrium running point shifted on the compressor characteristic, to counter the additional system pressure losses, and ensure a useful work output, albeit with a reduced surge margin. Solar-hybrid operation was only possible for solar share of at least 20%, while the work output and cycle thermal efficiency drop below standard operation levels beyond certain solar share. In contrast to standard operation, a higher nominal work output of 20 kW, at a lower S F C of 0.0004 kg/kWh and a higher cycle thermal efficiency of 8% was predicted, the latter potentially increasing to 20% with recuperation. Solar-hybrid equilibrium running could eliminate the risk of running into compressor surge. The findings from this study should guide operation and control strategies for the proposed, and future solar-hybrid MGT systems, which should in turn contribute to their development and commercialization. Highlights: The MGT system equilibrium running point shifted, reducing the surge margin. Solar-hybrid operation was only possible for solar share of at least 20%. Work output and cycle efficiency drop below standard MGT levels at given solar share. Sudden change in solar irradiation corrected by altering the fuel flow. Solar-hybrid equilibrium running could eliminate the risk of running into surge.